Caring masculinities at work in later life: Exploring relational care work in retirement - Miranda Leontowitsch (Gender, Work & Organization, 2022)
The paper reports on research that investigates older men's care practices and how their caring for others opens new ways of exploring the intersections of aging, gender, and care work. Using the concept caring masculinities as a sensitizing concept, the onus is on exploring patterns of power, interdependence, and relationality within men's care practices. Aging masculinities often remain constructed around paid-for occupational work (in opposition to unpaid care work) despite the transition into retirement. Little work exists on how caring is at work in later life potentially transforming gender relations and enacted masculinities. Moreover, much of the research on aging masculinities have not considered the expansiveness of retirement and the discourses as well as subjective expectations around the activity in later life that create an uncertain terrain of socioculturally structured mandates to be navigated. This paper draws on data from two qualitative interview studies conducted with retired men in England and Germany, in which the role of caregiving emerged as an inductive theme in their narratives. The paper makes a specific contribution to developing empirical and theoretical knowledge of caring masculinities and power relations by providing insights on men's trajectories into caring, and how they make sense of their caring for and about others.
Keywords: 300; caring masculinities; later life; men; power; reflexivity; relationality